Ground penetrating radar surveys in the archaeological area of Augusta Bagiennorum: Comparisons between geophysical and archaeological campaigns. Issue 3 (20th December 2021) - Colombero, Chiara; Comina, Cesare; Rocchietti, Deborah; Garbarino, Gian Battista; Sambuelli, Luigi
Abstract: Geophysical methods, and particularly ground penetrating radar (GPR), have been increasingly applied as a preliminary mapping tool to guide archaeological excavations. Direct comparisons between geophysical and archaeological features are however not always systematically performed given the different time spans, covered areas, acquisition and processing approaches of the surveys. A critical comparison between geophysical and archaeological results is here proposed on a test site within the archaeological area of Augusta Bagiennorum (NW Italy). Three rectangular sectors covering an area of approximately 2325 m 2 were investigated with high‐density GPR profiles and compared with both historical and new archaeological excavations. The GPR amplitude and attribute analyses highlight the effectiveness of geophysical prospections in identifying buried linear (i.e., walls) and localized (e.g., pillars or columns) archaeological remains. The recent archaeological excavations fully confirm the interpretation of the GPR results. Historical archaeological trenches, filled with coarse material after the excavation, are also found to generate strong anomalies in the GPR amplitude, similar to the ones of the buried structures, but with irregular contours and oblique orientations with respect to Roman remains. The GPR prospections also highlight interesting buried elements in unexplored areas, supporting important archaeological interpretations about the spatial configuration of the Roman city. The results help to recognize sectors with significant and well‐preserved buried remains that can be brought to light in the future to promote heritage conservation and enhancement at the site.